2015
DOI: 10.1371/journal.pone.0125897
|View full text |Cite
|
Sign up to set email alerts
|

DBA/2J Genetic Background Exacerbates Spontaneous Lethal Seizures but Lessens Amyloid Deposition in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a leading cause of dementia in the elderly and is characterized by amyloid plaques, neurofibrillary tangles (NFTs) and neuronal dysfunction. Early onset AD (EOAD) is commonly caused by mutations in amyloid precursor protein (APP) or genes involved in the processing of APP including the presenilins (e.g. PSEN1 or PSEN2). In general, mouse models relevant to EOAD recapitulate amyloidosis, show only limited amounts of NFTs and neuronal cell dysfunction and low but significant levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 57 publications
(60 reference statements)
1
30
0
Order By: Relevance
“…The present study was designed to explore the effects of the Rho GTPases’ modulator CNF1 on deputy biomarkers for seizures in the the neocortex. Particularly, we investigated the CNF1 effect on energy homeostasis and brain plasticity in the inbred strain of mice DBA/2J, a multipurpose neurological disease model that presents high susceptibility to induced [ 26 28 ] or spontaneous seizures [ 29 33 ], and the presence of spontaneous fast ripples [ 38 ]. We herein report that a single icv injection of CNF1 is able to raise a consistent and enduring antagonism to the spontaneous cortical EEG SWDs and HFOs (100–500 Hz range) during the physiological state of wakefulness in six-month-old DBA/2J mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was designed to explore the effects of the Rho GTPases’ modulator CNF1 on deputy biomarkers for seizures in the the neocortex. Particularly, we investigated the CNF1 effect on energy homeostasis and brain plasticity in the inbred strain of mice DBA/2J, a multipurpose neurological disease model that presents high susceptibility to induced [ 26 28 ] or spontaneous seizures [ 29 33 ], and the presence of spontaneous fast ripples [ 38 ]. We herein report that a single icv injection of CNF1 is able to raise a consistent and enduring antagonism to the spontaneous cortical EEG SWDs and HFOs (100–500 Hz range) during the physiological state of wakefulness in six-month-old DBA/2J mice.…”
Section: Discussionmentioning
confidence: 99%
“…D2 is a multipurpose neurological disease model because of its susceptibility to disorders that may involve neuronal cell damage including glaucoma [ 24 ] and hearing loss [ 25 ]. In particular, D2 genetic background is also of particular interest because of the high susceptibility to induced [ 26 28 ] or spontaneous seizures compared to other inbred strains [ 29 33 ]. Our hypothesis is that the ability of CNF1 to enhance mitochondrial ATP cortical level by modulation of mitochondrial dynamics [ 17 ], may favour a cell energy restoration and may re-estabilish the correct neuronal function in cortices of this mouse seizure model, similarly to what occurs in pathological models with a cognitive impairment [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, because of amino acid differences between the two species, mouse APP may be processed with little BACE1 cleavage and so may yield three times less Aβ than wildtype human APP (De Strooper et al, 1995 ). In addition, the genetic background of AD mouse strains affects a range of APP/Aβ phenotypes, including plaque deposition, APP metabolism, survival, and seizure rates (Carlson et al, 1997 ; Lehman et al, 2003 ; Krezowski et al, 2004 ; Lassalle et al, 2008 ; Rustay et al, 2010 ; Jackson et al, 2015 ). Similarly, phenotypes observed in DS mice may be influenced by genetic background (O'Doherty et al, 2005 ; Galante et al, 2009 ; Costa et al, 2010 ; Deitz and Roper, 2011 ; Haydar and Reeves, 2012 ).…”
Section: Studying Ad-ds Phenotypes In Micementioning
confidence: 99%
“…Later work using the YAC transgenic model R1.40 demonstrated that genetic background could influence both APP processing and the age at which amyloid deposits appeared, dramatically delaying onset from 13.5 months on C57BL/6 to >20 months on DBA/2 [ 115 ]. These two background strains also influenced phenotype in the APP/PS1 line 85 mice, where the DBA/2 background substantially increased susceptibility to lethal seizures compared to C57BL/6 [ 116 ]. Multiple genetic loci may contribute to these strain differences [ 117 ], including the kinesin light chain-1 gene identified as a modifier of amyloid onset in the DBA/2 background [ 118 ].…”
Section: Introductionmentioning
confidence: 99%